Gender Responsive Budgeting in India: Equality and Efficiency Dimension. - Devender Singh (2014)
As one of the important parts of public policy, national budget reflects the priority of the government on social and economic issues. Meanwhile, it reflects government’s political promises on specific policy and programmes. Social gender budget analysis makes the government able to take responsibility on the promises for social gender equity and human rights of women which links the distribution and use of public resources to production. Most governments have expressed a commitment to gender equality objectives and to gender mainstreaming, but often there is a gap between policy statements and the ways in which governments raise and spend money. Gender responsive budget initiatives can help to close these gaps, ensuring public money is raised and spent more effectively. They can help promote greater accountability for public resources to the people of a country, especially to women, who are generally more marginalised than men in decision-making about public money. In India, low level and inconsistent trends of expenditure on women specific and pro-women schemes confirm that Central Government has not integrated gender considerations into their budgeting process.